The Effectiveness of Problem-Based Learning Integrated with Culturally Responsive Teaching on Students’ Critical Thinking Abilities - Susilowati Susilowati; Maryati Maryati; Deni Sadly (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
The critical thinking ability of students in one seventh-grade class at a junior high school in Mlati District remains lacking. This is indicated by the low level of students’ performance in answering questions and actively participating in the learning process. Therefore, it is necessary to conduct research using the Integrated Problem-Based Learning Culturally Responsive Teaching (CRT) model to improve critical thinking skills. This study aims to evaluate the effectiveness of the Integrated Problem-Based Learning CRT model. The research employs classroom action research, following the Kemmis and Taggart model, which consists of four stages: planning, action, observation, and reflection. The study subjects were 32 students from a seventh-grade class. Data collection techniques included critical thinking ability tests and observations of the learning process. The study was conducted in two cycles. In Cycle I, the percentage of learning implementation reached 83%, with an N-gain value of 0.31 (moderate category), individual completeness of 73.60%, and classical completeness of 53.13%. Cycle II demonstrated improvement, with a learning implementation percentage of 97%, an N-gain value of 0.71 (in the high category), individual completeness of 89.68%, and classical completeness of 81.25%. These results suggest that learning using the PBL model integrated with CRT is effective in enhancing students’ critical thinking skills.